Plasmon-Assisted Efficiency Enhancement of Eu3+-Doped Tellurite Glass-Covered Solar Cells - Lima, Bismarck C.; Gómez-Malagón, L. A.; Gomes, A. S.L.; Garcia, J. A.M.; Kassab, L. R.P. [UNESP] (Springer Nature, 2017)
Rare-earth-doped tellurite glass containing metallic nanoparticles can be exploited to manage the solar spectrum in order to increase solar cell efficiency. It is therefore possible to modify the incident solar spectrum profile to the spectrum that optimizes the solar cell recombination process by covering the solar cell with plasmonic luminescent downshifting layers. With this approach, the losses due to thermalization are minimized and the efficiency is increased. Due to the down-conversion process that couples the plasmon resonance of the metallic nanoparticles and the rare-earth electronic energy levels, it is possible to convert photons from the ultraviolet region to the visible and near-band-gap region of the semiconductor. It is demonstrated here that plasmon-assisted efficiency enhancements of 14.0% and 34.5% can be obtained for commercial Si and GaP solar cells, respectively, covered with Eu3+-doped TeO2-ZnO glass containing silver nanoparticles.
Keywords: down-conversion; Photovoltaic cells; solar cell; tellurite glass